Vaginal Flora among Women with and without Bacterial Vaginosis - et.al, Rana S. Al-Taweel (Al-Qadisiyah Journal of Pure Science, 2017)
This study has been conducted in Al-Diwaniya city through the period from December 2012 to December 2013, in order to investigate the prevalence of bacterial vaginosis, and to compare the composition of vaginal flora between women with bacterial vaginosis (BV) and those without the syndrome. Results showed that, according to Nugent×³s scores, 18 women had BV with a prevalence of 16.07%. Culturing out of vaginal swabs from women has been revealed that coagulase-negative staphylococci were the dominant microorganisms in women without BV followed by lactobacilli (frequency of 20.63 and 16.66% respectively), while in BV patients the dominant microflora were non-hemolytic streptococci and coagulase-negative staphylococci (frequency, 21.95 and 17.07% respectively). Actinomyces israelii, has been isolated from a BV patient with a cervical ulcer, this result can assumed as a new record in Iraq .